Traumatic Intracranial Frontal Extradural Hematoma Associated with Orbital Subperiosteal Hematoma - Gupta, MK; Dhungel, K; Sah, PL; Ahmad, K; Rauniyar, RK (Nepalese Journal of Radiology, 2012)
Intracranial extradural hematoma (EDH) is a frequent lesion but simultaneous occurrence of EDH with orbital subperiosteal hematoma following head injury is a rare event. We report a 22 year old male who sustained head injury during road traffic accident. Glasgow coma scale was 13/15 on arrival and he had left orbital ecchymosis & subconjunctival hemorrhage. CT revealed left frontal extradural hematoma with associated orbital subperiosteal hematoma. No bone fracture was seen. The patient had good clinical recovery following surgical evacuation of the hematomas. DOI: http://dx.doi.org/10.3126/njr.v1i1.6325 Nepalese Journal of Radiology Vol.1(1): 52-53